Optimizing Human Resource Management in Madrasah Tsanawiyah - Oki Dermawan; Putri Octavia; Wan Jamaludin; Imam Syafi’i (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
This research examines the implementation of Sharia-based human resource management (HRM) in Madrasah Tsanawiyah Negeri 1-4 South Lampung. The scope of the study includes the planning and performance assessment of educators and educational staff, emphasizing sharia values. The research aims to investigate the closed and open planning systems applied in recruiting educators, family members of teachers, and collaboration with higher education institutions. Additionally, the study seeks to understand performance assessment practices. The research employs a combination of descriptive data analysis and qualitative approaches. Conducted at MTs Negeri 1-4 South Lampung, data collection involves observation, interviews with informants, and secondary data analysis from relevant literature. The findings indicate that the implementation of HRM involves a closed planning system through internal analysis and an open planning system through external recruitment by BKN. Performance assessments, although goal-based, face challenges in objectivity due to social relationships among staff members. In conclusion, the complexity of implementing Sharia-based HRM in Islamic education is evident. Further efforts are needed to enhance the objectivity of performance assessments, ensure accountability, and develop policies aligned with Sharia principles in the educational context. The implications of this research contribute to the development of more effective policies aligned with Sharia values.